Problem-Based Learning and Socio-Scientific Issues in Chemistry Education: Instructional Approaches, Learning Outcomes, and Research Trends - Sehati Mutiara Eljinsa; Endang W Laksono; Alfandi Ahmad (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
This systematic literature review examines the implementation of problem-based learning (PBL) integrated with socio-scientific issues (SSI) in chemistry education. The review aims to identify instructional approaches, chemistry learning contexts, reported learning outcomes, and emerging research trends related to SSI-PBL implementation in chemistry learning. The study followed the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. Literature searches were conducted through scopus, web of science (WoS), Taylor & Francis, ERIC, and google scholar, resulting in 24 selected studies published between 2020 and 2026. The findings indicate that SSI-PBL approaches were predominantly implemented through contextual and student-centered learning activities emphasizing inquiry, collaborative discussion, problem-solving, and evidence-based reasoning. Environmental chemistry and sustainability-related issues emerged as the most frequently used learning contexts, followed by indigenous chemistry, food safety, and nanotechnology topics. The reported learning outcomes included critical thinking, chemical literacy, problem-solving, argumentation, socio-scientific reasoning, sustainability awareness, and learning motivation. Most studies employed quantitative approaches such as pre-post-tests, N-gain analysis, t-tests, and Manova to evaluate learning effectiveness. The review also identified several emerging trends, including the increasing integration of sustainability and contextual SSI into chemistry learning. However, current research remains dominated by short-term quantitative interventions, while longitudinal studies, mixed-method approaches, and technology-supported SSI learning environments are still relatively limited. The findings suggest that SSI-PBL chemistry education has strong potential to support meaningful and contextual chemistry learning experiences connected to real-world socio-scientific problems